Targeted protein degradation at the host–pathogen interface. Issue 3 (2nd December 2021) - Grohmann, Christoph; Marapana, Danushka S.; Ebert, Gregor
Abstract: Infectious diseases remain a major burden to global health. Despite the implementation of successful vaccination campaigns and efficient drugs, the increasing emergence of pathogenic vaccine or treatment resistance demands novel therapeutic strategies. The development of traditional therapies using small‐molecule drugs is based on modulating protein function and activity through the occupation of active sites such as enzyme inhibition or ligand–receptor binding. These prerequisites result in the majority of host and pathogenic disease‐relevant, nonenzymatic and structural proteins being labeled "undruggable." Targeted protein degradation (TPD) emerged as a powerful strategy to eliminate proteins of interest including those of the undruggable variety. Proteolysis‐targeting chimeras (PROTACs) are rationally designed heterobifunctional small molecules that exploit the cellular ubiquitin‐proteasome system to specifically mediate the highly selective and effective degradation of target proteins. PROTACs have shown remarkable results in the degradation of various cancer‐associated proteins, and several candidates are already in clinical development. Significantly, PROTAC‐mediated TPD holds great potential for targeting and modulating pathogenic proteins, especially in the face of increasing drug resistance to the best‐in‐class treatments. In this review, we discuss advances in the development of TPD in the context of targeting the host–pathogen interface and speculate on their potential use to combat viral, bacterial, and parasitic infection. Abstract : Schematic representation of the catalytic mode of action of PROTACs to induce proteasomal degradation of host‐ and pathogen‐derived proteins in a mammalian cell. Current POIs amenable for TPD using PROTACs include host cell‐derived proteins and proteins derived from intracellular pathogens. With accessibility to the UPS being critical for TPD, cellular factors successfully used for TPD comprise cytoplasmic proteins, structural and scaffolding proteins, single‐ or multi‐pass transmembrane proteins including cell surface receptors, and cytosolic facing domains of mitochondria‐, ER‐, and Golgi network‐derived proteins, as well as nuclear proteins including transcription factors. Approaches that focus on the targeted degradation of intracellular pathogen‐derived proteins have been successfully demonstrated for various viruses. TPD approaches that affect bacterial pathogenicity factors are under development, but applicability has been already demonstrated in the proof of principle studies using BACTACs (indicated by opaque arrow). Importantly, TPD has the potential to be extended to parasites by recruitment of host or parasite E3 ligases (opaque arrow) and other intracellular pathogens (representation partly in the style of review by Burslem & Crews, 2020).